Factors influencing the perception of medical tourist in selection of their destination : a global perspective - Abd. Manaf, Noor Hazilah; Omar, Azura; Al Mamun Sarwar, Abdullah (2012)
There can be unlimited reasons why patients choose different countries while going for medical treatments or procedures. Moreover, empirical evidence on medical tourism is very limited. Due to the limited literature and empirical evidence on the topic, we believe that, other related studies focusing on the choice and criteria of selecting the destination will provide us with some useful insights and information on the factors influencing the patient’s perception in selecting the medical tourism destination in various countries around the world. The aim of this study is to present the theoretical and empirical literature on medical tourist’s perception on selecting the destination while going for medical treatment. It is organized into three main sections. First section focuses on the concepts, definitions and integrates the foregoing definitions of medical tourism and concepts of tourist’s perception of destination selection criteria and the theoretical framework. In section 2, an attempt is made to illustrate the impact of various reasons for selecting different destinations from the past findings. The final section deals with the conceptual framework of the study.